Local Government’s Effort for the Conservation of Rara Lake, Karnali, Nepal - Dahal, Girdhari (Janapriya Journal of Interdisciplinary Studies, 2023)
Rara, the largest Lake in Nepal, has enormous potential for the total development of the region. It is located in the Mugu district of Karnali region at an elevation of 2990 m. However, the federal and provincial governments’ current plans and strategies are ineffective in protecting and promoting the Lake from both present and future viewpoints. Participation theory was the most commonly used idea in this study. In order to provide baseline data for the formulation of efficient strategies and policies for the sustainable development of the Lake and its environs, this study intends to investigate the role of Rara Lake in the socioeconomic development of the Province. The study uses a questionnaire survey with a variety of stakeholders, including local people, business owners, and members of local political parties. The outcome shows that, in the current situation, the Lake’s promotion and conservation are solely dependent upon national park policies, as neither the provincial nor municipal governments have taken any direct action to further these goals. The results show that for the long-term conservation and promotion of the Lake, local inhabitants, and local government must adopt an integrated approach. The Lake would have a significant impact on the Province’s and the nation’s overall development if this strategy had been successfully applied.